Performance impact of different lower-limb setup positions in the backstroke swimming start - Barkwell, G. E. (University of Western Ontario, 2018)
The performance impact of different knee extension angles in the setup position for a backstroke start was evaluated using an instrumented starting surface. Ten backstroke swimmers completed maximum-effort starts in each of two setup positions: one with the knees flexed, and one with the knees extended. The start handles and touchpad were instrumented with tri-axial force plates. Activity of major hip and knee extensors was measured using surface electromyography. Body position was recorded throughout the start using two high-speed cameras. There was no difference in time to 10 m between the two conditions, indicating there is likely no advantage in universally recommending one setup position over the other. However, starts performed from a setup position with greater knee extension had a greater head entry distance, while starts from a setup position with less knee extension had a greater takeoff velocity; both of these variables are related to better start performance. Coaches should assess athletes to determine which position will result in better performance on an individual basis.